Atomically precise single-crystal structures of electrically conducting 2D metal–organic frameworks - Dou, Jin-Hu; Arguilla, Maxx Q.; Luo, Yi; Li, Jian; Zhang, Weizhe; Sun, Lei; Mancuso, Jenna L.; Yang, Luming; Chen, Tianyang; Parent, Lucas R.; Skorupskii, Grigorii; Libretto, Nicole J.; et al. (Nature materials, 2021)
Electrically conducting 2D metal–organic frameworks (MOFs) have attracted considerable interest, as their hexagonal 2D lattices mimic graphite and other 2D van der Waals stacked materials. However, understanding their intrinsic properties remains a challenge because their crystals are too small or of too poor quality for crystal structure determination. Here, we report atomically precise structures of a family of 2D π -conjugated MOFs derived from large single crystals of sizes up to 200 μm, allowing atomic-resolution analysis by a battery of high-resolution diffraction techniques. A designed ligand core rebalances the in-plane and out-of-plane interactions that define anisotropic crystal growth. We report two crystal structure types exhibiting analogous 2D honeycomb-like sheets but distinct packing modes and pore contents. Single-crystal electrical transport measurements distinctively demonstrate anisotropic transport normal and parallel to the π -conjugated sheets, revealing a clear correlation between absolute conductivity and the nature of the metal cation and 2D sheet packing motif. Two-dimensional MOFs can possess porosity and electrical conductivity but are difficult to grow as single crystals. Here, by balancing in-plane and out-of-plane interactions, single crystals of sizes up to 200 µm are grown, allowing in-plane transport measurements and atomic-resolution analysis.